Parâmetros químicos do óleo de pinhão-manso sob aplicação de água residuária da suinocultura: acidez e ácidos graxos - Frigo, Késia Damaris de Azevedo (2021)
The purpose of this paper, which is the study of the reuse of swine wastewater (SW) in the culture of physic nut (Jatropha curcas L.) and its influence on the acidity and quality of the obtained oi, is important since there is a rising demand for fuels, linked to the need to reduce the pollutants emission and the need to find adequate environmental management for pig breeding residues. Physic nut has characteristics of great importance to produce biofuel, as it is a plant that does not compete with the food sector, in addition to present high oil production and an easy adaptation to different soils and environments. The experiment was conducted in a 216 m² physic nut (Jatropha curcas L.) planting area where SW was applied three times a year with three months’ intervals. The seeds were harvested manually during the entire production period of the plant and the oil was extracted with the ethanol solvent. The chemical parameters of the obtained oil from physic nut were evaluated. The oil’s acidity and fatty acid composition were evaluated at the beginning and at the end of the experimental period. The statistical design was in completely randomized blocks, with the application of 0; 40; 80; 120; 160, and 200 m3 ha-1 under physic nut, totaling six treatments and three blocks. It was concluded that, although the doses 120 and 200 m3 ha-1 of SW provided an increase in the concentration of oleic and stearic fatty acids, for the lower acidity it is suggested that the application be carried out between 60 to 65 m3 ha-1 of SW. The application of SW under the culture of physic nut presents itself as an alternative of adequate reuse of this effluent and organic nutrition in the culture of the plant.